Effect of dislocation multiplication in intercritical region on microstructure and properties of low-carbon bainite/ferrite multiphase steel - TIAN Ya-qiang; TIAN Geng; WANG An-dong; ZHENG Xiao-ping; WEI Ying-li; SONG Jin-ying; CHEN Lian-sheng (工程科学学报, 2019)
Hot deformation is a way to effectively improve strength and plasticity of multiphase steels simultaneously, thereby, improving mechanical properties of multiphase steels. Hot deformation affects martensitic transformation mechanism, microstructure, and mechanical properties because it increases retained austenite content and improves stability of multiphase steels. Moreover, hot deformation plays a role in dislocation multiplication, and fine grain strengthening; it can reduce bainite transformation driving force, reduce bainite transformation point, and result in small multiphase organization after quenching-partitioning process. The result can significantly improve the properties of materials. The effects of high-temperature deformation on the stability of room-temperature microstructure, mechanical property, and retained austenite under treatment of IQ&PB (intercritical annealing-quenching and partitioning within the bainitic region) and DIQ&PB (intercritical deformation-intercritical annealing-quenching and partitioning within the bainitic region) processes were studied using scanning electron microscopy (SEM), transmission electron microscope (TEM), electron probe X-ray microanalyser (EPMA), X-ray diffraction (XRD), and tensile testing machine. The results show that dislocation density increases from 0.290×1014 to 1.286×1014 m-2 after 15% compression deformation, and the respective concentrations of C and Cu element enrichment in martensite (the original austenite) increases. Overall, dislocation multiplication produced by high-temperature deformation significantly promotes elemental distribution. After the deformation, the size of bainite lath shortenes and its width increases by 0.1 μm, the volume of the bainite transition increased by 14%, and the size of the polygonal ferrite significantly decreases under the DIQ&PB treatment. In terms of mechanical properties, the tensile strength increases by 132.85 MPa, and the elongation increases by 7%; the strength and ductility product reaches 25435 MPa·% after intercritical deformation heat treatment. The volume fraction of retained austenite increases from 7.8% to 8.99%, and the mass fraction of carbon in the retained austenite increases from 1.05% to 1.31% after compression deformation.